Biophysical studies on the structure-function relationship of membrane-active peptides - Pfeil, M (2016)
It is becoming evident that protein conformation and function are sensitive to the local environment. Structural models are often reported, out of technical necessity, in environments only partially related to the native environment of the protein of interest. This is a major challenge for structural biology of membrane proteins, which are predicted to be highly sensitive to their local environment. The structural plasticity of membrane-active alpha helical peptides and proteins is explored in native-like model membranes in this thesis. On the one hand, alpha helical antimicrobial peptides (AMPs) and their destructive membrane insertion mode are characterised, and on the other, the viroporin p7 (Hepatitis C Virus), expected to form oligomeric channels, is investigated in a endoplasmic reticulum mimicking model membrane. (I) AMPs: An engineering approach, which alters the antimicrobial insertion motif, is used to characterise distinct structure-function relationships linked between the primary and secondary peptide structures. Data is presented on different timescales and resolutions in order to understand the direct peptide location and orientation with respect to the membrane normal using solid-state NMR. Equally important are the global effects on the membrane bilayer and bacteria examined using atomic force microscopy (AFM) and fluorescence microscopy. Detailed dynamical changes and membrane order are explored by continuous wave EPR and solid-state NMR. Design principles that altered a pore-forming transmembrane AMP into a sequence that develops its potency in the membrane interface and shows broadspectrum antimicrobial activity are reported. (II) Different structural models of p7 have been reported in the literature, most of which are in a detergent or organic solvent environment. A single-constraint approach is presented in order to probe their plausibility in an endoplasmic reticulum-like model membrane using pulsed EPR. This is combined with angular constraints from solid-state NMR experiments in the same membrane composition. The results point towards an ensemble hairpin structure in the environment probed. Further to this, the drug-membrane interaction of the p7 inhibitor, NN-DNJ (an iminosugar), is investigated, and a membrane interaction is observed with a pKa of 6.3 for the membrane-partitioned inhibitor. Both systems are described in simplified models. While not yielding high resolution structures, these models are still an important consideration for the understanding of protein structure, topology and oligomerisation, which directly relates to protein function. The functionalities of the two systems explored in this thesis differ significantly, AMPs are naturally occurring antibiotics that compromise membrane integrity, whereas p7, with a defined channel architecture, is essential to the viral life cycle of Hepatitis C Virus. Hence, a structural spectrum of membrane-activity with relevance to infectious diseases is explored.